BmajPLA2-II, a basic Lys49-phospholipase A2 homologue from Bothrops marajoensis snake venom with parasiticidal potential - Grabner, Amy N.; Alfonso, Jorge; Kayano, Anderson M.; Moreira-Dill, Leandro S.; dos Santos, Ana Paula de A.; Caldeira, Cleópatra A.S.; Sobrinho, Juliana C.; Gómez, Ana; Grabner, Fernando P.; Cardoso, Fabio F. [UNESP]; Zuliani, Juliana Pavan; Fontes, Marcos R.M. [UNESP]; et al. (Elsevier, 2017)
Snake venoms contain various proteins, especially phospholipases A2 (PLA2s), which present potential applications in diverse areas of health and medicine. In this study, a new basic PLA2 from Bothrops marajoensis with parasiticidal activity was purified and characterized biochemically and biologically. B. marajoensis venom was fractionated through cation exchange followed by reverse phase chromatographies. The isolated toxin, BmajPLA2-II, was structurally characterized with MALDI-TOF (Matrix-assisted laser desorption/ionization-time of flight) mass spectrometry, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), followed by two-dimensional electrophoresis, partial amino acid sequencing, an enzymatic activity assay, circular dichroism, and dynamic light scattering assays. These structural characterization tests presented BmajPLA2-II as a basic Lys49 PLA2 homologue, compatible with other basic snake venom PLA2s (svPLA2), with a tendency to form aggregations. The in vitro anti-parasitic potential of B. marajoensis venom and of BmajPLA2-II was evaluated against Leishmania infantum promastigotes and Trypanosoma cruzi epimastigotes, showing significant activity at a concentration of 100 μg/mL. The venom and BmajPLA2-II presented IC50 of 0.14 ± 0.08 and 6.41 ± 0.64 μg/mL, respectively, against intraerythrocytic forms of Plasmodium falciparum with CC50 cytotoxicity values against HepG2 cells of 43.64 ± 7.94 and >150 μg/mL, respectively. The biotechnological potential of these substances in relation to leishmaniasis, Chagas disease and malaria should be more deeply investigated.
Keywords: Bothrops marajoensis; Chagas disease; Leishmaniasis; Malaria; Phospholipase A2; Snake venoms